PERILAKU MEMBOLOS PESERTA DIDIK DITINJAU DARI FAKTOR-FAKTOR YANG MELATARBELAKANGINYA - Wulan Dwiyanti Rahayu; Heris Hendriana; Siti Fatimah (IKIP Siliwangi, 2020)
This research was conducted based on a phenomenon that occurred at SMK Bunga Persada Cianjur with the aim of obtaining a picture of truancy behavior based on the factors behind it. The method used is a qualitative method with a descriptive type of research which is a case study. The data collection method used is by using interview guidelines. The results showed that the forms of truancy behavior carried out by students were coming to school late, not attending class during certain class hours, giving fake permits with artificial reasons and leaving the classroom without asking permission first. Meanwhile, the factors behind truancy behavior include being influenced by friends' invitations, less interest in some subjects and a tedious learning process. Keywords: Truancy Behavior, Factors behind Truancy, Students.